Determinants of Earnings Quality on Financial Sector Companies in Indonesia - Wachdaniyah, Eliisa Putri; Fitri, Alfiana (Universitas Pamulang, 2024)
Along with the movement of the growth rate of Gross Domestic Product (GDP) in Indonesia, which can describe economic conditions in a country, it is necessary to conduct research related to the quality of profits in the business sector, which is recorded as not experiencing growth contraction based on the Gross Domestic Product (GDP) data. This study examines the effect of managerial ownership, institutional ownership, independent boards of commissioners, audit committees, and prudence on earnings quality. The population in this study is represented by financial sector companies listed on the Indonesia Stock Exchange for 2017-2021. A purposive sampling method was used to determine the research sample, resulting in 48 companies that met the sample criteria. It is quantitative research using secondary data from the official website idx.co.id and determining the data analysis technique through multiple linear regression analysis. The findings of this study indicate that institutional ownership, independent board of commissioners, and prudence affect earnings quality. Meanwhile, managerial ownership and audit committees do not affect earnings quality.